Pathomorphological features of the proximal femur in crowe IV hips and their implication on stem selection during total hip arthroplasty - Kaveh Gharanizadeh; Elham Mohammadyahya; Mohammad Reza Bahaeddini; Shayan Amiri; Sajad Noori Gravand; Sepideh Pezeshki; Amir Aminian; Arvin Eslami; Hamed Tayyebi; Mansour Abolghasemian (BMC Musculoskeletal Disorders)
Abstract Background The best stem type and location for femoral shortening in high-riding developmental dysplasia of the hip (DDH) in not clear. We evaluated the morphology of the proximal femur on EOS™ images, focusing on the anatomical landmarks and measurements relevant to the stem selection in high-riding DDH. Our goal is to identify and define the differences in the anatomy of the proximal femur between patients with Crowe type IV DDH and normal individuals, in order to determine the appropriate neck cut location in these patients to increase the chances of successfully using a wedge femoral stem. Methods EOS™ images of 40 hips with Crowe type-IV DDH and 40 normal hips were included. The distances between the tip of the greater trochanter and vastus ridge (GT-VR), vastus ridge and proximal border of lesser trochanter (VR-LT), greater- and lesser trochanters (GT-LT), base width of the LT, and the proportion of these distances to the femoral length were evaluated. Canal Flare Index (CFI) was also measured, at two different levels. Results The mean GT-LT index was not different between the two groups (p = 0.46). The GT-VR index was smaller in the case group (p < 0.001), while the VR-LT index was greater (p < 0.001). The LT base width index was larger in the case group (P < 0.001). CFI was smaller at the LT level in dysplastic hips (P < 0.001), but the values were similar with a cut 1.5 cm above the LT (P = 0.67). Conclusion In Crowe IV hips, the GT height is shorter and the LT is located far more distally along the femoral metaphysis, resulting in a narrower canal width at the upper border of the lesser trochanter. Also, the CFI at the LT level is smaller, and to fit a wedge stem, the neck cut should be made at a higher level.